2012
DOI: 10.1258/ar.2012.120218
|View full text |Cite
|
Sign up to set email alerts
|

CT angiography of intracranial arterial vessels: impact of tube voltage and contrast media concentration on image quality

Abstract: The uses of highly concentrated contrast media and low tube voltage are easily performed measures to improve image quality in CTA of intracranial vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Although many studies have proposed the prevention of contrast-induced nephropathy, the practical clinical settings for minimization of iodine amount have remained unchanged [8], [9], which are mainly due to the fact that a reduction in the effective iodine amount may attenuate the enhancement of vessels and consequently adversely affect diagnostic accuracy [36], [37]. By using low tube voltage technique, a better vascular enhancement can be achieved with less iodine amount.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have proposed the prevention of contrast-induced nephropathy, the practical clinical settings for minimization of iodine amount have remained unchanged [8], [9], which are mainly due to the fact that a reduction in the effective iodine amount may attenuate the enhancement of vessels and consequently adversely affect diagnostic accuracy [36], [37]. By using low tube voltage technique, a better vascular enhancement can be achieved with less iodine amount.…”
Section: Discussionmentioning
confidence: 99%
“…Such lowkilovolt protocols are used in cerebral perfusion CT in the evaluation of patients with stroke 16 and in pediatric CT. 17 In phantom 18 as well as in clinical studies, it has been demonstrated that this technique can also be used in chest and abdominal imaging in adults. [19][20][21][22][23][24] Lower tube voltage in CTA results in higher noise levels on one hand, but the attenuation of iodine is increased 25,26 on the other hand. This relationship must be considered when trying to reduce radiation exposure by use of low-kilovolt scanning and to maintain image quality.…”
mentioning
confidence: 99%
“…This relationship must be considered when trying to reduce radiation exposure by use of low-kilovolt scanning and to maintain image quality. 24,27 The higher noise level in low-kilovolt scans will not be completely compensated by the higher iodine attenuation; therefore, additional adjustments of the tube current (milliampere setting) are necessary. Optimal manual adjustment of these parameters is complex, which prevented low-kilovolt scanning from general use until now.…”
mentioning
confidence: 99%
“…The use of relatively smaller CM volumes in combination with higher flow rates indicates an inferior importance of CM volume and TIL compared with flow rate and IDR with respect to arterial enhancement, even under emergency conditions: IDR can be manipulated by adjusting either flow rate or iodine concentration of CM [IDR (gI s 21 ) 5 flow rate (ml s 21 ) 3 iodine concentration (gI ml 21 )]. Some authors state that attenuation in CTA could be increased by using higher iodine concentrations of CM, 28 whereas others state that increasing IDR-by increasing flow rate-is the most influencing factor regarding CM enhancement. 16,29 Increasing flow rate might be preferable for optimizing CM application for CTA, since increasing iodine concentration of CM simultaneously increases CM viscosity.…”
Section: Discussionmentioning
confidence: 99%